3‐Bromo N‐Alkyl Cyanamides as Versatile Building Blocks. Issue 1 (14th December 2018) - Wright, Karen; Drouillat, Bruno; Menguy, Laurence; Marrot, Jérôme; Couty, François
Abstract : 3‐Bromo N ‐alkyl cyanamides are accessible in one simple synthetic operation from N ‐alkyl azetidines reacting with cyanogen bromide. These unexplored building blocks combine two extremely useful electrophilic moieties: an alkyl bromide and a cyanamide. We demonstrate herein that they can be transformed into a range of nitrogen‐containing molecules, and especially cyclic guanidines, accessible in enantiomerically pure form. Considering the large structural diversity of available azetidines, this contribution complements the use of these strained heterocycles in diversity‐oriented synthesis. Abstract : 3‐Bromo N ‐alkyl cyanamides, obtained by the reaction of azetidines with cyanogen bromide, are useful bis‐electrophiles. Their reaction with amines, significantly accelerated by microwave heating, led to the formation of cyclic guanidines.